Worship and culture : foreign country or homeland? - d (Grand Rapids, Michigan ; Cambridge, U.K. : William B. Eerdmans Publishing Company, 2014)
How are we to proclaim Christ in different cultures? This question was central to a landmark study on worship and culture conducted by the Lutheran World Federation between 1992 and 1952. Much has changed in the years since then: the world today more than ever is a multicultural global village. Worship and Culture revisits that LWF study and publication, shedding new light on the question from recent theological and sociological scholarship to expand and enrich the texts in the original three-volume work. This book includes texts from the main statements that came out of the original project as well as updated essays from some of the original contributors. It also adds new essays, prayers, and hymns to the conversation, inviting readers to consider what the life of the church should look like in today's hybrid, multicultural world.
From the past to the future : the LWF study series on worship and culture as vision and mission / Norman A. Hjelm -- Every foreign country a homeland, every homeland a foreign country : on worship and culture / Gordwon W. Lathrop -- The Cartigny statement on worship and culture : biblical and historical foundations / Lutheran World Federation, 1993 -- Christian worship : toward localization and globalization / S. Anita Stauffer -- What then do theologians mean when they say " culture"? / Benjamin M. Stewart -- Vatican II and the LWF project : points of convergence / Margaret Mary Kelleher -- Reenvisioning "liturgy and the components of culture" / Anscar J. Chupungco -- Context, margins, and ministry : a church in the Pacific Northwest's "none zone" / Scott Anderson -- Dynamics of world musics : a methology for evaluation / Mark P. Bangert -- The last word? : Dynamics of world musics twenty years later / Mark P. Bangert -- The Nairobi statement on worship and culture / Lutheran World Federation, 1996 -- A fragile future for the ordo? / Stephen Burns -- Worship : translating the untranslatable / Dirk G. Lange -- Inculturation : God's mission and the crucian "old year's night" liturgy / Joseph A. Donnella II -- Worship : ecumenical core and cultural context / S. Anita Stauffer -- Christian unity and Christian diversity , lessons from liturgical renewal : the case of the Christian Church (Disciples of Christ) / Thomas F. Best -- Worship with a Brazilian face : dialogue between culture and worship as a way of caring for and transforming life / t
Includes bibliographical references and index.
Keywords: Worship; Christianity and culture; Lutheran World Federation